Penerapan Metode TOPSIS Pada Sistem Pendukung Keputusan Dalam Pemberian Penghargaan Kepada Pegawai Non-ASN Teladan Pada Dinas Kebudayaan Provinsi Bali - I Made Agus Oka Gunawan; Gusti Komang Tri Wismana; I Putu Bagus Ambara Yasa; Putu Dian Karmana (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
The main decision support system for measuring or assessing the performance of an employee in a government agency is very important especially to be used as a condition for getting an award. However, current employee performance appraisals still use subjective judgments, so that it will cause differences in the results of the assessment based on who will judge. One method that can be applied in a decision support system is the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS). At the Government Office of the Cultural Office of the Province of Bali, which in this case is a Regional Government Organization that wants to analyze the performance appraisal of NON-ASN employees to help solve problems in employee appraisal, will provide alternative solutions which are one of the accurate benchmarks to get appropriate results. Based on the calculation results, it can be concluded that using the TOPSIS method in selecting exemplary employees will provide convenience in carrying out analytical calculations for determining exemplary NON-ASN employees within the Bali Province Cultural Agency.